Characterization of diabase core anisotropy: Integrating ultrasonic measurements and digital rock physics - Setiawan, Muhamad Ragil; Fatkhan; Latief, Fourier Dzar Eljabbar; Fauzi, Umar (Journal of applied geophysics, 2025)
As intricate compositions of diverse materials, hard rock possesses complex mechanical and elastic properties influenced by various factors. In this study, a diabase core was drilled, characterized, measured, and analyzed to investigate the elastic properties of rocks. The research aims to evaluate these properties using dynamic and static methods, employing ultrasonic measurements and digital rock physics. The sample underwent mineralogical analysis through thin sections. Comparatively, micro-CT scanning was employed to explore potential layering and fractures that might impact the anisotropy of acoustic wave propagation, as observed in digital images. The digital image reveals the presence of high-density minerals, particularly Clinopyroxene, extending along the z-axis. The static and dynamic elastic moduli suggest that the sample exhibits isotropic characteristics. However, variations in anisotropy coefficient values for Vp and Vs are noted, likely stemming from high-density sheet-like minerals. While both static and dynamic methods produce elastic moduli and velocities within the typical range for diabase rock, notable differences are apparent, possibly due to disparities in the physical techniques utilized. •A diabase rock is cored from subsurface and characterized using petrophysics.•The ultrasonic measurement of compressional and shear wave velocity for anisotropy and elastic properties calculation.•3D scanning was carried out to obtain digital rock images using micro-CT scan.•The effective elastic properties and anisotropy from digital rock core is calculated.•The difference between dynamic and static elastic properties, velocity, and anisotropy of the diabase rock is analyzed.